Early Cretaceous paleomagnetic results from Marie Byrd Land, West Antarctica: Implications for the Weddellia collage of crustal blocks - DiVenere, Victor J.; Kent, Dennis V.; Dalziel, I. W. D. (1995)
A new ~117 Ma paleomagnetic pole has been defined from the study of volcanic and plutonic rocks from the eastern portion Marie Byrd Land (MBL). The new pole (185.6°E/56.8°S, A_95 = 8.7°) implies that the eastern portion of MBL was an integral part of Weddellia, which included the ancestral Antarctic Peninsula, Thurston Island, and Ellsworth-Whitmore Mountains blocks of West Antarctica. This pole is generally similar to a ~125 Ma pole from Thurston Island. Both poles call for major clockwise rotation and poleward motion of eastern MBL and Thurston Island between the Early Cretaceous (125-117 Ma) and the mid-Cretaceous (110-100 Ma). We propose that in the Early Cretaceous, eastern MBL and the Eastern Province of New Zealand were part of a continuous active Pacific margin of Gondwana, connecting with the Antarctic Peninsula, and distinct from western MBL, the Western Province of New Zealand, and North Victoria Land. These western terranes are thought to have accreted to Gondwana in the Devonian. Eastern MBL and the Eastern Province of New Zealand amalgamated with western MBL and the Western Province of New Zealand by the mid-Cretaceous. Major Early Cretaceous motions of the Weddellia blocks postdate the estimated initiation of seafloor spreading in the Weddell Sea and therefore may be the result of plate reorganization during the Cretaceous Quiet Zone.